Rare earth-WC-Co-Ni composite powder and preparation method thereof, ultrafine-grained cemented carbide and preparation method thereof
By using rare earth-WC-Co-Ni composite powder and using oxygen-rich calcining, hydrogen reduction and carbonization processes, the problem of abnormal growth of WC grains in ultrafine crystal carbides is solved, and higher hardness and bending strength are achieved.
Patent Information
- Application Number
- CN202411974995.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-04
AI Technical Summary
The existing ultrafine crystal carbides are prone to abnormal growth during low-pressure sintering, resulting in unstable material performance and cannot meet the hardness and bending strength requirements for practical applications.
Rare earth-WC-Co-Ni composite powder is prepared through oxygen-rich calcination, hydrogen reduction and carbonization steps to ensure uniform distribution of components such as WC, Co, Ni and rare earth oxides to inhibit grain growth.
Effectively reduce the grain size of cemented carbide, improve hardness and bending strength, and achieve tissue uniformity and performance stability.
Smart Images

Figure HDA0005220244040000011 
Figure HDA0005220244040000012 
Figure HDA0005220244040000013
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of cemented carbide materials, and in particular to a rare earth-WC-Co-Ni composite powder and a preparation method thereof, and an ultrafine-grained cemented carbide and a preparation method thereof. Background Art
[0002] Cemented carbide is widely used in electronic information, oil and gas mining, mineral exploration, aerospace, national defense and military industries due to its excellent properties such as high hardness, high strength and good wear resistance. With the rapid development of modern electronic information technology, higher requirements are also put forward for ultrafine-grained cemented carbide tools. Improving the hardness and strength of ultrafine-grained cemented carbide can not only extend the service life, but also improve the hole position accuracy, hole wall smoothness and drilling speed; and improving the uniformity of the structure of ultrafine-grained cemented carbide is an important guarantee for its processing stability. Therefore, the preparation of ultrafine-grained rare earth WC-Co-Ni cemented carbide with uniform structure and stable performance is conducive to promoting the miniaturization and high integration of electronic devices, and is of great significance to promoting the rapid development of industries such as smart terminals, computers and network equipment, industrial control and automobiles.
[0003] The key to improving the uniformity of cemented carbide organization and the stability of performance is to ensure the fine-grained structure of cemented carbide. Abnormally grown grains will seriously affect the mechanical properties of cemented carbide. At present, traditional ultrafine-grained cemented carbide mainly adopts powder metallurgy technology, and ultrafine WC powder, bonding phase metal powder, and inhibitor powder are mixed by ball milling and sintered. However, the method of directly adding grain inhibitors during ball milling is prone to uneven distribution of inhibitors, and still cannot effectively inhibit the abnormal growth of WC grains during low-pressure sintering, which seriously deteriorates the material properties. For example, the prior art provides a rare earth nickel-based cemented carbide, whose hardness can reach 90.5HRA and flexural strength can reach 3150MPa, but its hardness and flexural strength still cannot meet the needs of practical applications. Summary of the invention
[0004] The object of the present invention is to provide a rare earth-WC-Co-Ni composite powder and a preparation method thereof, an ultrafine-grained cemented carbide and a preparation method thereof. The ultrafine-grained rare earth-WC-Co-Ni composite powder provided by the present invention can effectively reduce the grain size of the cemented carbide and improve the hardness and bending strength of the cemented carbide.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0006] The invention provides a rare earth-WC-Co-Ni composite powder, which comprises, by mass percentage, 75-90% of WC, 7-15% of Co, 2.5-10% of Ni, 0.2-1% of VC, 0.2-1% of Cr3C2 and 0.1-1% of rare earth oxide.
[0007] Preferably, the rare earth-WC-Co-Ni composite powder comprises, by mass percentage, 78-88% WC, 8-12% Co, 3.5-8% Ni, 0.3-0.8% VC, 0.3-0.8% Cr3C2 and 0.2-0.8% rare earth oxide.
[0008] Preferably, the rare earth-WC-Co-Ni composite powder comprises, by mass percentage, 80-85% WC, 9-10% Co, 5-6% Ni, 0.5-0.6% VC, 0.5-0.6% Cr3C2 and 0.3-0.5% rare earth oxide.
[0009] Preferably, the rare earth element is Y, La or Ce.
[0010] The present invention also provides a method for preparing the rare earth-WC-Co-Ni composite powder described in the above technical solution, comprising the following steps:
[0011] (1) drying the mixed solution of each metal salt and then performing a first grinding to obtain a precursor fine powder;
[0012] (2) subjecting the precursor powder obtained in step (1) to oxygen-enriched calcination and then to a second grinding to obtain an oxidized composite powder;
[0013] (3) reducing the oxidized composite micropowder obtained in step (2) with hydrogen to obtain reduced composite micropowder;
[0014] (4) grinding and mixing the reduced composite powder obtained in step (3) with a carbonizing agent for a third time and then carbonizing the mixture to obtain a rare earth-WC-Co-Ni composite powder.
[0015] Preferably, the atmosphere of the oxygen-enriched calcination in step (2) is oxygen with a volume concentration of 5 to 20%, the temperature of the oxygen-enriched calcination is 400 to 700° C., the heating rate of the oxygen-enriched calcination is 4 to 10° C. / min, and the time of the oxygen-enriched calcination is 1 to 3 hours.
[0016] Preferably, in step (4), the carbonization temperature is 900-1200° C., the carbonization heating rate is 4-10° C. / min, and the carbonization time is 1-3 h.
[0017] The present invention also provides a method for preparing ultrafine-grained rare earth-WC-Co-Ni hard alloy, comprising:
[0018] The rare earth-WC-Co-Ni composite powder is mixed with a forming agent and then pressed to obtain a compact; the rare earth-WC-Co-Ni composite powder is the rare earth-WC-Co-Ni composite powder described in the above technical solution or the rare earth-WC-Co-Ni composite powder prepared by the preparation method described in the above technical solution;
[0019] The compact is sintered to obtain an ultrafine-grained rare earth-WC-Co-Ni hard alloy.
[0020] Preferably, the sintering temperature is 1200-1400° C., the sintering pressure is 2-6 MPa, and the sintering time is 30-60 min.
[0021] The present invention also provides an ultrafine-grained rare earth-WC-Co-Ni hard alloy prepared by the preparation method described in the above technical solution.
[0022] The invention provides a rare earth-WC-Co-Ni composite powder, which comprises, by mass percentage, 75-90% of WC, 7-15% of Co, 2.5-10% of Ni, 0.2-1% of VC, 0.2-1% of Cr3C2 and 0.1-1% of rare earth oxide. The rare earth-WC-Co-Ni composite powder provided by the present invention realizes uniform distribution of alloy components, effectively inhibits abnormal grain growth, and improves the mechanical properties of cemented carbide materials; when the rare earth-WC-Co-Ni composite powder is pressure sintered, an appropriate amount of WC serves as a hard phase in the alloy to provide basic hardness and strength for the alloy; an appropriate amount of Co can be filled in the gaps between WC particles, so that the WC particles are bonded to each other to form an overall structure, and the hardness and strength of the alloy are effectively improved; an appropriate amount of Ni can partially replace Co in the alloy, absorb energy through its own plastic deformation, reduce the generation and expansion of cracks, and further improve the performance of the cemented carbide; an appropriate amount of rare earth oxide has the function of purifying grain boundaries and enhancing the toughness of the alloy, and further optimizes the mechanical properties of the alloy; an appropriate amount of V and Cr can form hard carbides, which are dispersed in the gaps between WC particles, inhibit the growth of WC grains, greatly refine the alloy grains, and further improve the hardness and bending strength of the cemented carbide. The results of the examples show that the cemented carbide prepared from the rare earth-WC-Co-Ni composite powder provided by the present invention has a grain size of 0.3-0.5 μm, a hardness of 92.1-93.2 HRA, and a bending strength of 4100-4650 MPa. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 is a SEM image of the rare earth-WC-Co-Ni composite powder of Example 1 at a magnification of 10,000 times;
[0024] Figure 2 The SEM image of the rare earth-WC-Co-Ni composite powder of Example 1 is magnified 50,000 times
[0025] Figure 3 is a SEM image of the ultrafine-grained rare earth-WC-Co-Ni cemented carbide of Example 6 at a magnification of 1500 times;
[0026] Figure 4 This is a SEM image of the ultrafine-grained rare earth-WC-Co-Ni cemented carbide of Example 6 at a magnification of 10,000 times. DETAILED DESCRIPTION
[0027] The invention provides a rare earth-WC-Co-Ni composite powder, which comprises, by mass percentage, 75-90% of WC, 7-15% of Co, 2.5-10% of Ni, 0.2-1% of VC, 0.2-1% of Cr3C2 and 0.1-1% of rare earth oxide.
[0028] In terms of mass percentage, the rare earth-WC-Co-Ni composite powder provided by the present invention includes 75-90% WC. As an embodiment of the present invention, the mass content of the WC can be 78-88%, or 80-85%; in an embodiment of the present invention, the mass content of the WC can be specifically 75%, 76%, 78%, 79%, 80%, 83%, 85%, 86%, 88% or 90%. In the present invention, an appropriate amount of WC can be used as a hard phase in the cemented carbide prepared from the composite powder to provide basic hardness and strength for the alloy.
[0029] In terms of mass percentage, the rare earth-WC-Co-Ni composite powder provided by the present invention includes Co 7-15%. As an embodiment of the present invention, the Co can be 8-12%, or 9-10%. In an embodiment of the present invention, the mass content of the Co can be specifically 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10%, 11%, 12%, 14% or 15%. In the present invention, an appropriate amount of Co can be used as a bonding phase in the cemented carbide prepared from the composite powder, filling the gaps between the WC particles, so that the WC particles are bonded to each other to form an overall structure, effectively improving the hardness and strength of the alloy.
[0030] In terms of mass percentage, the rare earth-WC-Co-Ni composite powder provided by the present invention includes 2.5-10% Ni. As an embodiment of the present invention, the mass content of Ni can be 3.5-8%, or 5-6%; in an embodiment of the present invention, the mass content of Ni can be specifically 2.5%, 3%, 3.5%, 4%, 5%, 5.5%, 6%, 7%, 8%, 9% or 10%. In the present invention, an appropriate amount of Ni can achieve partial substitution of Co in the cemented carbide prepared from the composite powder, absorb energy through its own plastic deformation, reduce the generation and expansion of cracks, and further improve the performance of the cemented carbide.
[0031] In terms of mass percentage, the rare earth-WC-Co-Ni composite powder provided by the present invention includes VC 0.2-1%. As an embodiment of the present invention, the mass content of the VC can be 0.3-0.8%, or 0.5-0.6%. In an embodiment of the present invention, the mass content of the VC can be specifically 0.2%, 0.25%, 0.3%, 0.4%, 0.5%, 0.55%, 0.6%, 0.7%, 0.8%, 0.9% or 1%. In the present invention, an appropriate amount of VC can further suppress the growth of WC grains in the cemented carbide prepared from the composite powder, refine the alloy grains, and further improve the mechanical properties of the alloy.
[0032] In terms of mass percentage, the rare earth-WC-Co-Ni composite powder provided by the present invention includes 0.2-1% of Cr3C2. As an embodiment of the present invention, the mass content of the Cr3C2 can be 0.3-0.8%, or 0.5-0.6%. In an embodiment of the present invention, the mass content of the Cr3C2 can be specifically 0.2%, 0.25%, 0.3%, 0.4%, 0.5%, 0.55%, 0.6%, 0.7%, 0.8%, 0.9% or 1%. In the present invention, an appropriate amount of Cr3C2 can form hard carbides, which are dispersed in the gaps between WC particles, further improving the hardness and bending strength of the cemented carbide prepared from the composite powder.
[0033] In terms of mass percentage, the rare earth-WC-Co-Ni composite powder provided by the present invention includes 0.1-1% of rare earth oxide. As an embodiment of the present invention, the mass content of the rare earth oxide can be 0.2-0.8%, or 0.3-0.5%; in an embodiment of the present invention, the mass content of the rare earth oxide can be specifically 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.8%, 0.9% or 1%. In the present invention, an appropriate amount of rare earth oxide has the effect of purifying grain boundaries and enhancing alloy toughness, further optimizing the mechanical properties of the alloy.
[0034] As an embodiment of the present invention, the rare earth oxide may be an oxide of Y, La or Ce, or an oxide of Y. In the present invention, by limiting the types of rare earth elements, the rare earth elements can fully play their role, further improving the mechanical properties of the cemented carbide prepared from the composite powder.
[0035] The rare earth-WC-Co-Ni composite powder provided by the present invention can effectively inhibit the abnormal growth of WC grains during sintering under the joint action of various components, which is beneficial to improving the mechanical properties of cemented carbide; at the same time, the composite powder is used as a cemented carbide raw material to ensure uniform cemented carbide structure and further improve the hardness and bending strength of the cemented carbide.
[0036] The present invention also provides a method for preparing the rare earth-WC-Co-Ni composite powder described in the above technical solution, comprising the following steps:
[0037] (1) drying the mixed solution of each metal salt and then performing a first grinding to obtain a precursor fine powder;
[0038] (2) subjecting the precursor powder obtained in step (1) to oxygen-enriched calcination and then to a second grinding to obtain oxidized composite powder;
[0039] (3) reducing the oxidized composite micropowder obtained in step (2) with hydrogen to obtain reduced composite micropowder;
[0040] (4) grinding and mixing the reduced composite powder obtained in step (3) with a carbonizing agent for a third time and then carbonizing the mixture to obtain a rare earth-WC-Co-Ni composite powder.
[0041] The present invention performs a first grinding after drying the mixed solution of each metal salt to obtain precursor fine powder.
[0042] As an embodiment of the present invention, the metal salt solutions may be ammonium metatungstate, cobalt salt, nickel salt, vanadyl oxalate, chromium nitrate and rare earth salt; in the embodiment of the present invention, the cobalt salt may be cobalt acetate, cobalt nitrate or cobalt sulfate; the nickel salt may be nickel acetate, nickel nitrate or nickel sulfate; the rare earth salt may be yttrium acetate, lanthanum acetate, cerium acetate, yttrium nitrate, lanthanum nitrate or cerium nitrate. In the present invention, the composition of the composite powder is ensured by limiting the type of metal salt; at the same time, the use of metal salt solution as a reaction raw material can effectively improve the uniform distribution of each element in the precursor micropowder, effectively improve the composition uniformity of the precursor micropowder, and further improve the composition uniformity of the composite powder.
[0043] As an embodiment of the present invention, the purity of the ammonium metatungstate, vanadyl oxalate and chromium nitrate can be independently ≥99.9%, or 99.99%; the purity of the cobalt salt, nickel salt and rare earth salt can be independently ≥99.5%, or ≥99.9%. In the present invention, by limiting the purity of the metal salt, the introduction of impurities into the composite powder is avoided, and the mechanical properties of the composite powder and cemented carbide are further improved.
[0044] As an embodiment of the present invention, the mixed solution can be obtained by mixing saturated solutions of various metal salts.
[0045] As an embodiment of the present invention, the drying can be forced air drying; the drying temperature can be 90-120°C, or 100-110°C; the drying time can be 4-8h, or 5-6h. In the present invention, the water in the mixed solution is fully removed by limiting the process parameters of the drying process.
[0046] As an embodiment of the present invention, the rotation speed of the first grinding can be 3000-4000rpm / min, 3200-3800rpm / min, or 3500-3600rpm / min; the time of the first grinding can be 10-60min, 20-50min, or 30-40min. In the present invention, by limiting the process parameters of the first grinding process, the mixed material obtained after the metal salt mixed solution is dried can be fully ground, which is conducive to the subsequent calcination reaction.
[0047] As an embodiment of the present invention, the particle size of the precursor powder may be 100-200 meshes; when the particle size of the precursor powder is not within the above-defined range, it may be sieved with a 100-200 mesh screen after the first grinding.
[0048] After obtaining the precursor micropowder, the present invention performs oxygen-enriched calcination on the precursor micropowder and then performs a second grinding to obtain oxidized composite micropowder.
[0049] As an embodiment of the present invention, the atmosphere of the oxygen-enriched calcination can be oxygen with a volume concentration of 5-20%, 8-15%, or 10-12%; the temperature of the oxygen-enriched calcination can be 400-700°C, 450-650°C, or 500-600°C; the heating rate of the oxygen-enriched calcination can be 4-10°C / min, 5-8°C / min, or 6-7°C / min; the time of the oxygen-enriched calcination can be 1-3h, 1.5-2.5h, or 1.8-2h. In the present invention, oxygen-enriched calcination converts each metal salt into a metal oxide. By limiting the process parameters of the oxygen-enriched calcination process, the precursor powder is fully calcined, the formation of a regular and dense crystal structure is promoted, the mechanical properties of the cemented carbide prepared by the composite powder are further improved, and the crystallinity is further reduced.
[0050] As an embodiment of the present invention, the second grinding speed can be 3000-4000rpm / min, 3200-3800rpm / min, or 3500-3600rpm / min; the second grinding time can be 10-60min, 20-50min, or 30-40min. In the present invention, by limiting the process parameters of the grinding process, it is ensured that the oxidized precursor powder is fully ground, which is conducive to the subsequent reduction reaction.
[0051] As an embodiment of the present invention, the particle size of the oxidized composite micropowder is 200-325 meshes; when the particle size of the oxidized composite micropowder is not within the above-defined range, it can be sieved with a 200-325 mesh sieve after the second grinding.
[0052] After obtaining the oxidized composite micropowder, the present invention reduces the oxidized composite micropowder with hydrogen to obtain reduced composite micropowder.
[0053] As an embodiment of the present invention, the reduction temperature can be 750-900°C, 780-850°C, or 800-820°C; the reduction time can be 2-4h, 2.5-3.8h, or 2.8-3h. In the present invention, the reduction reaction can reduce tungsten oxide to form metal alloy powders NiW, CoW, and W powder, and other metal components in the oxidized composite powder are also reduced to metal alloy powders; by limiting the process parameters of the reduction operation process, the oxidized composite powder is fully reduced, the composition and phase structure of the composite powder are regulated, and the growth of grains can be inhibited, further improving the hardness and bending resistance of the alloy.
[0054] After obtaining the reduced composite micropowder, the present invention grinds and mixes the reduced composite micropowder with a carbonizing agent for a third time and then carbonizes the mixture to obtain a rare earth-WC-Co-Ni composite powder.
[0055] As an embodiment of the present invention, the carbonizing agent may be carbon black.
[0056] As an embodiment of the present invention, the mass ratio of the reduced composite powder to the carbonizing agent can be (93.7-93.85):(6.15-6.3), or (93.75-93.8):(6.2-6.25). In the present invention, by limiting the mass ratio of the reduced composite powder to the carbonizing agent, it is ensured that the W in the reduced composite powder can be fully carbonized.
[0057] As an embodiment of the present invention, the rotation speed of the third grinding and mixing can be 3000-4000rpm / min, 3200-3800rpm / min, or 3500-3600rpm / min; the time of the third grinding and mixing can be 10-60min, 20-50min, or 30-40min. In the present invention, by limiting the process parameters of the grinding process, the reduced composite micropowder and the carbonizing agent are uniformly mixed, which is conducive to the subsequent carbonization reaction.
[0058] As an embodiment of the present invention, the carbonization temperature can be 900-1200°C, 950-1100°C, or 1000-1050°C; the carbonization heating rate can be 4-10°C / min, 5-8°C / min, or 6-7°C / min; the carbonization time can be 1-3h, 1.5-2.5h, or 1.8-2h. In the present invention, the carbonization process causes the metals W, V, and Cr to be carbonized, and hard phases WC and Cr3C2 can be formed; by limiting the process parameters of the carbonization process, the carbonization effect is further improved, and the hardness and strength of the cemented carbide obtained from the composite powder are further improved.
[0059] As an embodiment of the present invention, the carbonization can be carried out under an inert atmosphere; the inert atmosphere can be hydrogen or argon. In the present invention, by limiting the inert atmosphere of the carbonization reaction, the formation of oxides is avoided to affect the mechanical properties of the cemented carbide obtained from the composite powder.
[0060] The preparation method provided by the present invention adopts oxygen-enriched calcination, which is conducive to obtaining a composite powder with more complete crystallization; by carbonizing after low-temperature reduction, accurate carbonizing in the carbonization process can be achieved, reducing carbon loss; at the same time, the composite powder preparation process is divided by grinding treatment to effectively control the particle size of the composite powder, avoiding the agglomeration and coarse inclusion problems of the composite powder in the preparation process, making the obtained composite powder uniform in structure, and further improving the mechanical properties of the cemented carbide prepared by the composite powder.
[0061] The present invention also provides a method for preparing ultrafine-grained rare earth-WC-Co-Ni hard alloy, comprising:
[0062] The rare earth-WC-Co-Ni composite powder is mixed with a forming agent and then pressed to obtain a compact; the rare earth-WC-Co-Ni composite powder is the rare earth-WC-Co-Ni composite powder described in the above technical solution or the rare earth-WC-Co-Ni composite powder prepared by the preparation method described in the above technical solution;
[0063] The compact is sintered to obtain an ultrafine-grained rare earth-WC-Co-Ni hard alloy.
[0064] The invention mixes rare earth-WC-Co-Ni composite powder with a forming agent and then performs pressing to obtain a compact.
[0065] In the present invention, the rare earth-WC-Co-Ni composite powder is the rare earth-WC-Co-Ni composite powder described in the above technical solution or the rare earth-WC-Co-Ni composite powder prepared by the preparation method described in the above technical solution.
[0066] As an embodiment of the present invention, the mass ratio of the rare earth-WC-Co-Ni composite powder to the forming agent can be (97.5-98.5):(1.5-2.5), or (97.8-98.2):(1.8-2.2). In the present invention, by limiting the mass ratio of the rare earth-WC-Co-Ni composite powder to the forming agent, sufficient contact reaction between the two is ensured, thereby promoting the forming of the composite powder.
[0067] As an embodiment of the present invention, the molding agent may be polyethylene glycol. In the present invention, by limiting the type of the molding agent, the molding effect of the composite powder is further improved.
[0068] As an embodiment of the present invention, the mixing method may be ball milling; as an embodiment of the present invention, the ball milling may be wet milling; the medium of the wet milling is ethanol; the rotation speed of the ball milling may be 80-120 rpm / min, or 90-100 rpm / min; the time of the ball milling may be 3-12 hours, or 5-10 hours, or 6-8 hours; the ball-to-material ratio of the ball milling may be (3-8):1, or (4-7):1, or (5-6):1. In the present invention, by limiting the process parameters of the ball milling process, the ball milling effect is ensured, the agglomeration of the composite powder and the forming agent is effectively avoided, and the component segregation is prevented, so as to further improve the mechanical properties of the alloy.
[0069] As an embodiment of the present invention, the drying temperature can be 80-100°C, or 85-90°C; the drying time can be 3-8h, or 4-5h. In the present invention, by limiting the process parameters of the drying process, ethanol in the mixture of the composite powder and the molding agent is effectively removed, which is beneficial to the subsequent molding.
[0070] As an embodiment of the present invention, the pressure of the press molding can be 80-150MPa, 90-130MPa, or 100-120MPa; the time of the press molding can be 10-60s, 20-50s, or 30-40s. In the present invention, by limiting the process parameters of the press molding, the press effect is improved, which is beneficial to the uniformity of the subsequent sintering.
[0071] After obtaining the compact, the present invention sintered the compact to obtain ultrafine grain rare earth-WC-Co-Ni hard alloy.
[0072] In the present invention, the sintering atmosphere can be argon; the sintering pressure can be 2-6MPa, 3-5MPa, or 3.5-4MPa; the sintering temperature can be 1200-1400°C, 1250-1350°C, or 1300-1320°C; the sintering time can be 30-60min, 35-55°C, or 40-50°C. In the present invention, Ni and Co form a solid solution during the sintering process, which serves as a bonding phase to connect the hard phase WC; V and Cr exist in the form of carbides VC and Cr3C2, which serve as grain inhibitors to effectively reduce the grain size of the cemented carbide, inhibit abnormal grain growth, and form ultrafine-grained WC-Co-Ni cemented carbide; by limiting the process parameters of the sintering process, the sintering effect is further improved, the uniform heating of the pressed green sheet is ensured, and the mechanical properties of the ultrafine-grained rare earth-WC-Co-Ni cemented carbide are further improved.
[0073] The method for preparing ultrafine-grained rare earth-WC-Co-Ni cemented carbide by using composite powder provided by the present invention is beneficial to further improve the agglomeration problem of the composite powder and further improve the hardness and strength of the cemented carbide.
[0074] The present invention also provides an ultrafine-grained rare earth-WC-Co-Ni hard alloy prepared by the above preparation method.
[0075] The ultrafine-grained rare earth-WC-Co-Ni hard alloy provided by the invention has low grain size, high hardness and high bending strength.
[0076] In order to further illustrate the present invention, the rare earth-WC-Co-Ni composite powder and its preparation method, ultrafine-grained cemented carbide and its preparation method provided by the present invention are described in detail below in combination with the embodiments, but they should not be understood as limiting the scope of protection of the present invention.
[0077] Example 1
[0078] A rare earth-WC-Co-Ni composite powder, which consists of 85% WC, 9% Co, 4.5% Ni, 0.4% VC, 0.6% Cr3C2 and 0.5% Y2O3 in terms of mass percentage;
[0079] The method for preparing the rare earth-WC-Co-Ni composite powder comprises the following steps:
[0080] (1) Mix saturated solutions of ammonium metatungstate, cobalt acetate, nickel nitrate, vanadyl oxalate, chromium nitrate and yttrium nitrate, dry them with air at 110° C. for 5 h, grind them for the first time at 3500 rpm / min for 20 min, and pass them through a 100-mesh sieve to obtain precursor powder; wherein the purity of ammonium metatungstate, vanadyl oxalate and chromium nitrate is 99.9%, and the purity of cobalt acetate, nickel nitrate and yttrium nitrate is 99.5%;
[0081] (2) adding the precursor powder obtained in step (1) into a calcining furnace, calcining in an atmosphere with an oxygen concentration of 15% at 650° C. for 1.5 h, then grinding the precursor powder for a second time at a speed of 3500 rpm / min for 40 min using a grinding mill, and passing the powder through a 200-mesh sieve to obtain an oxidized composite powder;
[0082] (3) adding the oxidized composite micropowder obtained in step (2) into a reduction furnace and performing hydrogen reduction at 780° C. for 3.5 hours to obtain reduced composite micropowder;
[0083] (4) The reduced composite powder obtained in step (3) with a mass ratio of 93.87:6.13 and the carbonizing agent are ground and mixed for a third time at a speed of 3200 rpm / min using a grinding mill for 20 minutes. After the third grinding, argon gas is filled in, and the temperature is raised to 950° C. at a rate of 5° C. / min for carbonization for 2 hours to obtain a rare earth-WC-Co-Ni composite powder.
[0084] The rare earth-WC-Co-Ni composite powder obtained in Example 1 was detected by scanning electron microscopy, and the SEM image obtained with a magnification of 10,000 times was as follows: Figure 1 The SEM image obtained with a magnification of 50,000 times is shown in Figure 2 As shown. Figure 1 and Figure 2 It can be seen that the rare earth-WC-Co-Ni composite powder of Example 1 has fine particles, is relatively evenly dispersed, and has no agglomeration phenomenon.
[0085] Example 2
[0086] A rare earth-WC-Co-Ni composite powder, which consists of 88% WC, 8% Co, 2.8% Ni, 0.3% VC, 0.63% Cr3C2 and 0.6% CeO2 by mass percentage;
[0087] The method for preparing the rare earth-WC-Co-Ni composite powder comprises the following steps:
[0088] (1) Mixing saturated solutions of ammonium metatungstate, cobalt nitrate, nickel nitrate, vanadyl oxalate, chromium nitrate and cerium acetate, drying them by forced air at 100° C. for 7 h, and then grinding them for 30 min at a speed of 3600 rpm / min using a mill, and passing them through a 150-mesh sieve to obtain precursor powder; wherein the purity of ammonium metatungstate, vanadyl oxalate and chromium nitrate is 99.9%, and the purity of cobalt nitrate, nickel nitrate and cerium acetate is 99.5%;
[0089] (2) adding the precursor powder obtained in step (1) into a calcining furnace, calcining in an atmosphere with an oxygen concentration of 18% at 450° C. for 3 h, then grinding the precursor powder for a second time at a speed of 3200 rpm / min using a grinding mill for 40 min, and passing the powder through a 275-mesh sieve to obtain an oxidized composite powder;
[0090] (3) adding the oxidized composite micropowder obtained in step (2) into a reduction furnace and performing hydrogen reduction at 820° C. for 2 h to obtain reduced composite micropowder;
[0091] (4) The reduced composite powder obtained in step (3) with a mass ratio of 93.83:6.17 and the carbonizing agent are ground and mixed for a third time at a speed of 3300 rpm / min using a grinding mill for 10 minutes. After the third grinding, argon gas is filled in, and the temperature is raised to 1150° C. at a rate of 6° C. / min for carbonization for 1 hour to obtain a rare earth-WC-Co-Ni composite powder.
[0092] Example 3
[0093] A rare earth-WC-Co-Ni composite powder, which consists of 80% WC, 12% Co, 6.5% Ni, 0.4% VC, 0.8% Cr3C2 and 0.3% La2O3 by mass percentage;
[0094] The method for preparing the rare earth-WC-Co-Ni composite powder comprises the following steps:
[0095] (1) Mixing saturated solutions of ammonium metatungstate, cobalt nitrate, nickel acetate, vanadyl oxalate, chromium nitrate and lanthanum acetate, drying them by forced air at 90° C. for 8 h, and then grinding them for 40 min at a speed of 3400 rpm / min using a mill, and passing them through a 200-mesh sieve to obtain precursor powder; wherein the purity of ammonium metatungstate, vanadyl oxalate and chromium nitrate is 99.9%, and the purity of cobalt nitrate, nickel acetate and lanthanum acetate is 99.5%;
[0096] (2) adding the precursor powder obtained in step (1) into a calcining furnace, calcining in an atmosphere with an oxygen concentration of 10% at 500° C. for 1.5 h, then grinding the precursor powder for a second time at a speed of 3600 rpm / min using a grinding mill for 30 min, and passing the powder through a 250-mesh sieve to obtain an oxidized composite powder;
[0097] (3) adding the oxidized composite micropowder obtained in step (2) into a reduction furnace and performing hydrogen reduction at 800° C. for 2.5 hours to obtain reduced composite micropowder;
[0098] (4) The reduced composite powder obtained in step (3) with a mass ratio of 93.85:6.15 and the carbonizing agent are ground and mixed for a third time at a speed of 3600 rpm / min using a grinding mill for 10 minutes. After the third grinding, argon gas is filled in, and the temperature is raised to 1050° C. at a rate of 8° C. / min for carbonization for 1.5 hours to obtain a rare earth-WC-Co-Ni composite powder.
[0099] Example 4
[0100] A rare earth-WC-Co-Ni composite powder, which consists of 82% WC, 8% Co, 8% Ni, 0.8% VC, 0.3% Cr3C2 and 0.9% Y2O3 in terms of mass percentage;
[0101] The method for preparing the rare earth-WC-Co-Ni composite powder comprises the following steps:
[0102] (1) Mixing saturated solutions of ammonium metatungstate, cobalt acetate, nickel acetate, vanadyl oxalate, chromium nitrate and yttrium acetate, drying them by forced air at 100° C. for 6 h, and then grinding them for 20 min at a speed of 3800 rpm / min using a mill, and passing them through a 150-mesh sieve to obtain precursor powder; wherein the purity of ammonium metatungstate, vanadyl oxalate and chromium nitrate is 99.9%, and the purity of cobalt acetate, nickel acetate and yttrium acetate is 99.5%;
[0103] (2) adding the precursor powder obtained in step (1) into a calcining furnace, calcining in an atmosphere with an oxygen concentration of 5% at 600° C. for 2.5 h, then grinding the precursor powder for a second time at a speed of 3300 rpm / min using a grinding mill for 30 min, and passing the powder through a 300-mesh sieve to obtain an oxidized composite powder;
[0104] (3) adding the oxidized composite micropowder obtained in step (2) into a reduction furnace and performing hydrogen reduction at 860° C. for 3 h to obtain reduced composite micropowder;
[0105] (4) The reduced composite powder obtained in step (3) with a mass ratio of 93.81:6.19 and the carbonizing agent are ground and mixed for a third time at a speed of 300 rpm / min using a grinding mill for 30 minutes. After the third grinding, argon gas is filled in, and the temperature is increased to 1000° C. at a rate of 30° C. / min for carbonization for 2.5 hours to obtain a rare earth-WC-Co-Ni composite powder.
[0106] Example 5
[0107] A rare earth-WC-Co-Ni composite powder, which consists of 75% WC, 13.3% Co, 10% Ni, 0.7% VC, 0.6% Cr3C2 and 0.4% CeO2 by mass percentage;
[0108] The method for preparing the rare earth-WC-Co-Ni composite powder comprises the following steps:
[0109] (1) Mixing saturated solutions of ammonium metatungstate, cobalt nitrate, nickel nitrate, vanadyl oxalate, chromium nitrate and cerium acetate, drying them by forced air at 120° C. for 4 h, and then grinding them for 50 min at a speed of 3200 rpm / min using a mill, and passing them through a 100-mesh sieve to obtain precursor powder; wherein the purity of ammonium metatungstate, vanadyl oxalate and chromium nitrate is 99.9%, and the purity of cobalt nitrate, nickel nitrate and cerium acetate is 99.5%;
[0110] (2) adding the precursor powder obtained in step (1) into a calcining furnace, calcining in an atmosphere with an oxygen concentration of 9% at 550° C. for 3.5 h, then grinding the precursor powder for a second time at a speed of 3500 rpm / min using a grinding mill for 30 min, and filtering the powder through a 200-mesh sieve to obtain an oxidized composite powder;
[0111] (3) adding the oxidized composite micropowder obtained in step (2) into a reduction furnace and performing hydrogen reduction at 920° C. for 2 h to obtain reduced composite micropowder;
[0112] (4) The reduced composite powder obtained in step (3) with a mass ratio of 93.84:6.16 and the carbonizing agent are ground and mixed for a third time at a speed of 3600 rpm / min using a grinding mill for 20 minutes. After the third grinding, argon gas is filled in, and the temperature is raised to 900° C. at a rate of 7° C. / min for carbonization for 3 hours to obtain a rare earth-WC-Co-Ni composite powder.
[0113] Example 6
[0114] A method for preparing ultrafine-grained rare earth-WC-Co-Ni cemented carbide:
[0115] The rare earth-WC-Co-Ni composite powder obtained in Example 1 was mixed with polyethylene glycol in a mass ratio of 98.5:1.5, and ball milled for 6 hours at a rotation speed of 100 rpm / min and a ball-to-material ratio of 5:1, and then dried at 90°C for 3 hours. After drying, a molding machine was used to press the powder to obtain a compact; wherein the pressing pressure was 110 MPa and the pressing time was 20 seconds;
[0116] The compact is placed in a low-pressure degreasing and sintering integrated furnace, filled with argon, and sintered at 4 MPa and 1250° C. for 60 minutes to obtain an ultrafine-grained rare earth-WC-Co-Ni cemented carbide.
[0117] The ultrafine-grained rare earth-WC-Co-Ni cemented carbide obtained in Example 6 was detected by scanning electron microscopy, and the SEM image obtained with a magnification of 1500 times is as follows: Figure 3 The SEM image obtained with a magnification of 10,000 times is shown in Figure 4 As shown. Figures 3-4 It can be seen that the cemented carbide obtained in Example 6 has a uniform microstructure, the WC grains in the alloy are uniform and fine, there are no abnormally grown large-sized grains, the overall alloy microstructure is clear and uniform, and no defective phases appear.
[0118] Example 7
[0119] A method for preparing ultrafine-grained rare earth-WC-Co-Ni cemented carbide:
[0120] The rare earth-WC-Co-Ni composite powder obtained in Example 2 was mixed with polyethylene glycol in a mass ratio of 97.8:2.2, and then ball-milled for 9 hours at a rotation speed of 80 rpm / min and a ball-to-material ratio of 3:1, and then dried at 80°C for 5 hours. After drying, a mold press was used to press the green compact, wherein the pressing pressure was 100 MPa and the pressing time was 30 seconds;
[0121] The compact is placed in a low-pressure degreasing and sintering integrated furnace, filled with argon, and sintered at 5 MPa and 1350° C. for 45 minutes to obtain an ultrafine-grained rare earth-WC-Co-Ni cemented carbide.
[0122] Example 8
[0123] A method for preparing ultrafine-grained rare earth-WC-Co-Ni cemented carbide:
[0124] The rare earth-WC-Co-Ni composite powder obtained in Example 3 was mixed with polyethylene glycol in a mass ratio of 97.5:2.5, and ball milled for 4 hours at a rotation speed of 120 rpm / min and a ball-to-material ratio of 6:1, and then dried at 100°C for 5 hours. After drying, a mold press was used to press the green compact, wherein the pressing pressure was 130 MPa and the pressing time was 20 seconds;
[0125] The compact is placed in a low-pressure degreasing and sintering integrated furnace, filled with argon, and sintered at 3 MPa and 1300° C. for 60 minutes to obtain an ultrafine-grained rare earth-WC-Co-Ni cemented carbide.
[0126] Example 9
[0127] A method for preparing ultrafine-grained rare earth-WC-Co-Ni cemented carbide:
[0128] The rare earth-WC-Co-Ni composite powder obtained in Example 4 was mixed with polyethylene glycol in a mass ratio of 98.2:1.8, and ball milled for 6 hours at a rotation speed of 90 rpm / min and a ball-to-material ratio of 8:1, and then dried at 100°C for 5 hours. After drying, a mold press was used to press the green compact, wherein the pressing pressure was 110 MPa and the pressing time was 40 seconds;
[0129] The compact is placed in a low-pressure degreasing and sintering integrated furnace, filled with argon, and sintered at 4 MPa and 1400° C. for 30 minutes to obtain an ultrafine-grained rare earth-WC-Co-Ni cemented carbide.
[0130] Example 10
[0131] A method for preparing ultrafine-grained rare earth-WC-Co-Ni cemented carbide:
[0132] The rare earth-WC-Co-Ni composite powder obtained in Example 5 was mixed with polyethylene glycol in a mass ratio of 98:2, and ball milled for 10 hours at a rotation speed of 110 rpm / min and a ball-to-material ratio of 5:1, and then dried at 90°C for 7 hours. After drying, a molding machine was used to press the powder to obtain a compact; wherein the pressing pressure was 90 MPa and the pressing time was 60 seconds;
[0133] The compact is placed in a low-pressure degreasing and sintering integrated furnace, filled with argon, and sintered at 5 MPa and 1200° C. for 60 minutes to obtain an ultrafine-grained rare earth-WC-Co-Ni cemented carbide.
[0134] Comparative Example 1
[0135] A WC-Co-Ni composite powder, which consists of 85% WC, 9% Co, 4.5% Ni, 0.4% VC and 1.1% Cr3C2 by mass percentage;
[0136] The difference between the preparation method of the rare earth-WC-Co-Ni composite powder and the preparation method in Example 1 is that no rare earth element is added, and steps (2), (3) and (4) are combined into one step, and a one-step reduction carbonization method is adopted. The specific operation is: oxygen-enriched calcination at 650°C for 1.5 hours in a hydrogen atmosphere, hydrogen reduction at 780°C for 3.5 hours and carbonization at 950°C for 2 hours. The rest is the same as in Example 1.
[0137] Comparative Example 2
[0138] The difference between Comparative Example 2 and Example 1 is that in the preparation method, steps (2), (3) and (4) are combined into one step, and a one-step reduction carbonization method is adopted. The specific operation is: oxygen-enriched calcination at 650°C for 1.5 h in a hydrogen atmosphere, hydrogen reduction at 780°C for 3.5 h and carbonization at 950°C for 2 h; the rest is the same as Example 1.
[0139] Comparative Example 3
[0140] The difference between Comparative Example 3 and Example 1 is only in the composition of the rare earth-WC-Co-Ni composite powder. No rare earth element is added. In terms of mass percentage, the composite powder is composed of WC 85%, Co 9%, Ni 4.5%, VC 0.4% and Cr3C21.1%. The other components are the same as those in Example 1.
[0141] Comparative Example 4
[0142] The only difference between Comparative Example 4 and Example 6 is that the WC-Co-Ni composite powder of Comparative Example 1 is used to prepare the cemented carbide.
[0143] Comparative Example 5
[0144] The only difference between Comparative Example 5 and Example 6 is that the rare earth-WC-Co-Ni composite powder of Comparative Example 2 is used to prepare the cemented carbide.
[0145] Comparative Example 6
[0146] The only difference between Comparative Example 6 and Example 6 is that the WC-Co-Ni composite powder of Comparative Example 3 is used to prepare the cemented carbide.
[0147] The grain size of the ultrafine-grained rare earth-WC-Co-Ni cemented carbide was detected by scanning electron microscopy, and the detection standard was GB / T 3488.2-2018; the hardness of the ultrafine-grained rare earth-WC-Co-Ni cemented carbide was detected by Rockwell hardness tester, and the detection standard was GB / T 3849.1-2015; the bending strength of the ultrafine-grained rare earth-WC-Co-Ni cemented carbide was detected by universal mechanical testing machine, and the detection standard was GB / T 3851-2015. The results are shown in Table 1.
[0148] Table 1 Mechanical properties of cemented carbides of Examples 6 to 10 and Comparative Examples 4 to 6
[0149] Example Grain size (μm) Hardness (HRA) Flexural strength(MPa) Example 6 0.3 93.2 4400 Example 7 0.5 93.6 4100 Example 8 0.3 92.7 4350 Example 9 0.4 93 4200 Example 10 0.3 92.1 4650 Comparative Example 4 0.9 90.8 2870 Comparative Example 5 0.8 91.7 3220 Comparative Example 6 0.7 90.5 3570
[0150] It can be seen from Table 1 that the ultrafine-grained rare earth-WC-Co-Ni cemented carbide provided by the present invention has a low grain size, indicating that the cemented carbide provided by the present invention has a fine-grained structure, which avoids the deterioration of the mechanical properties of the alloy caused by abnormal grain growth; and the cemented carbide provided by the present invention has excellent hardness and bending strength.
[0151] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A rare earth-WC-Co-Ni composite powder, which comprises, by mass percentage, 75-90% WC, 7-15% Co, 2.5-10% Ni, 0.2-1% VC, 0.2-1% Cr3C2 and 0.1-1% rare earth oxide.
2. The rare earth-WC-Co-Ni composite powder according to claim 1, characterized in that: Calculated by mass percentage, it includes WC78-88%, Co 8-12%, Ni 3.5-8%, VC 0.3-0.8%, Cr3C20.3-0.8% and rare earth oxide 0.2-0.8%.
3. The rare earth-WC-Co-Ni composite powder according to claim 2, characterized in that: Calculated by mass percentage, it includes WC 80-85%, Co 9-10%, Ni 5-6%, VC 0.5-0.6%, Cr3C25-0.6% and rare earth oxide 0.3-0.5%.
4. The ultrafine rare earth-WC-Co-Ni composite powder according to any one of claims 1 to 3, characterized in that: The rare earth element is Y, La or Ce.
5. The method for preparing the rare earth-WC-Co-Ni composite powder according to any one of claims 1 to 4, comprising the following steps: (1) drying the mixed solution of each metal salt and then performing a first grinding to obtain a precursor fine powder; (2) subjecting the precursor powder obtained in step (1) to oxygen-enriched calcination and then to a second grinding to obtain an oxidized composite powder; (3) reducing the oxidized composite micropowder obtained in step (2) with hydrogen to obtain reduced composite micropowder; (4) grinding and mixing the reduced composite powder obtained in step (3) with a carbonizing agent for a third time and then carbonizing the mixture to obtain a rare earth-WC-Co-Ni composite powder.
6. The preparation method according to claim 5, characterized in that: The atmosphere of the oxygen-enriched calcination in step (2) is oxygen with a volume concentration of 5 to 20%, the temperature of the oxygen-enriched calcination is 400 to 700° C., the heating rate of the oxygen-enriched calcination is 4 to 10° C. / min, and the time of the oxygen-enriched calcination is 1 to 3 hours.
7. The preparation method according to claim 5, characterized in that: In the step (4), the carbonization temperature is 900-1200° C., the carbonization heating rate is 4-10° C. / min, and the carbonization time is 1-3 h.
8. A method for preparing ultrafine-grained rare earth-WC-Co-Ni cemented carbide, characterized in that: include: The rare earth-WC-Co-Ni composite powder is mixed with a forming agent and then pressed to obtain a compact; the rare earth-WC-Co-Ni composite powder is the rare earth-WC-Co-Ni composite powder according to any one of claims 1 to 4 or the rare earth-WC-Co-Ni composite powder prepared by the preparation method according to any one of claims 5 to 7; The compact is sintered to obtain an ultrafine-grained rare earth-WC-Co-Ni hard alloy.
9. The preparation method according to claim 8, characterized in that: The sintering temperature is 1200-1400° C., the sintering pressure is 2-6 MPa, and the sintering time is 30-60 min.
10. Ultrafine-grained rare earth-WC-Co-Ni cemented carbide prepared by the preparation method according to claim 8 or 9.
Citation Information
Cited By
High-entropy rare earth doped WC hard alloy and preparation method and application thereof
CN121178840A